Soil organic amendments with Polygonum cuspidatum residues enhance growth, leaf gas exchange, and bioactive component levels - Liu, Lei; Mu, Hong-Na; Zhang, Ze-Zhi (Frontiers in Plant Science, 2025)
The extracted residue of Polygonum cuspidatum (a valuable medicinal plant) rhizome is discarded as waste, while it is unclear whether returning this residue to the field would be beneficial for the growth and its active component production of P. cuspidatum. This study aimed to investigate the effects of applying P. cuspidatum residues (PRs) to the field on plant growth, photosynthetic activities, root indole-3-acetic acid (IAA) and zeatin riboside (ZR) levels, active component (polydatin, resveratrol, and emodin) contents, and the expression of resveratrol-associated genes (PcRS and PcPKS1) in P. cuspidatum plants. The experiment comprised four treatments, namely, the application of potassium sulfate compound fertilizer at a rate of 50 kg/667 m2 and the application of PRs at rates of 1500 kg/667 m2 (PR1500), 2500 kg/667 m2 (PR2500), and 4000 kg/667 m2 (PR4000), along with a control (CK) receiving no additional substances. Two years later, the application of both the compound fertilizer and PR treatments led to substantial increases in plant height, stem diameter, leaf number, number of nodes on main stems, and aboveground (leaf, branch, and main stem) and root biomass production, depending on used doses of PRs applied. Among them, the PR2500 treatment exhibited the superior performance. Additionally, these treatments significantly boosted root IAA (11.0−41.7%) and ZR (17.8−46.0%) levels, with the PR2500 treatment demonstrating the highest efficacy. Root IAA and ZR levels were significantly (p < 0.01) positively correlated with root biomass. All treatments, except for PR4000, significantly elevated SPAD values, net photosynthesis rate, transpiration rate, and intercellular CO2 concentration in leaves, with PR2500 showing the most pronounced improvements. Fertilization and PR treatments significantly boosted root polydatin (6.6−22.0%), emodin (12.1−43.3%), and resveratrol (17.8−69.3%, except for PR4000) levels, along with a significant up-regulation of PcRS expression and a significant down-regulation of PcPKS1 expression in roots. In short, organic amendments like PRs, particularly at a rate of 2500 kg/667 m2, can be a viable alternative to traditional fertilizers for enhancing the plant growth and its active component levels of P. cuspidatum, making them a cornerstone of eco-friendly farming practices and sustainable agriculture.